Privacy in the age of facebook : discourse, architecture, consequences - Raynes-Goldie, Kate Sarah (Curtin University, 2012)
Most academic and journalistic discussions of privacy on Facebook have centred on users, rather than the company behind the site. The result is an overwhelming focus on the perceived shortcomings of users with respect to irresponsible privacy behaviours, rather than an examination of the potential role that Facebook Inc. may have in encouraging such behaviours. Aiming to counterbalance this common technologically deterministic perspective, this thesis deploys a multi-layered ethnographic approach in service of a deep and nuanced analysis of privacy on Facebook. This approach not only looks at both the users and creators of Facebook, it examines Facebook Inc. in the context of historical, cultural and discursive perspectives.Specifically, this thesis details how the company's privacy policy and design decisions are guided not simply by profit, but by a belief system which which encourages "radical transparency" (Kirkpatrick, 2010) and is at odds with conventional understandings of privacy. In turn, drawing on Fiske's model of popular culture, users "make do" with the limited privacy choices afforded them by the site, while at the same time attempting to maximise its social utility. As this dynamic demonstrates, Facebook Inc. plays a critical, yet often overlooked role in shaping privacy norms and behaviours through site policies and architecture. Taken together, the layers of this thesis provide greater insight into user behaviour with respect to privacy, and, more broadly, demonstrate the importance of including critical analyses of social media companies in examinations of privacy culture.